HILARY OF POITIERS AND THEOLOGICAL LANGUAGE - B. van de Beek (Acta Theologica)
Hilary of Poitiers deals with the question concerning our knowledge of God. Knowledge of God will never be attained by human efforts. God is only known through Jesus who is God in the human flesh. We learn this not from philosophy, but from the apostle John. The reality of God in Christ precedes our knowledge of God, and this knowledge dominates language. The word “Trinity” refers to this knowledge, but it has no meaning apart from the confession that Christ is homoousios with both the Father and the Spirit. Consequently, Hilary does not attempt to render the Trinity understandable. It is simply another word for homoousios.